International entrepreneurial marketing in the digital era - Yang Man; Torkkeli Lasse (Edward Elgar Publishing, 2025)
International entrepreneurial marketing is a powerful marketing practice for international firms, and literature has argued that it is an important yet often neglected driver of successful entrepreneurial internationalization. Marketing approaches globally have been transformed through digitalization in both research and practice, yet literature has provided little knowledge on the application of international entrepreneurial marketing in the digital era. This research thus describes the role and importance of international entrepreneurial marketing for future research agenda in international entrepreneurship, by developing a conceptual framework and by positing that international entrepreneurial marketing influences positively the international digital marketing strategy of entrepreneurial firms. The study helps in integrating literature on international marketing and digital international entrepreneurship, thus contributing to international entrepreneurship. The present study outlines the main arising theoretical and managerial implications and considers the ways in which the present study paves the way for future research on international entrepreneurial marketing in international entrepreneurship.
A Research Agenda for International Entrepreneurship